Concerns of hemodialysis patients - Benetou, Sofia; Tsirigotis, Stavros; Dousis, Evangelos; Alikari, Victoria; Evangelou, Eleni; Koutelekos, Ioannis; Zartaloudi, Afroditi; Gerogianni, Georgia (Health & Research Journal, 2020)
Introduction: Hemodialysis, which is the most common treatment in individuals with end stage renal disease, includes a series of limitations and modifications in daily life that adversely affect patients’ physical and psychological state. Eliciting and addressing patients’ concerns is a key aspect of patient-centered treatment. Unaddressed concerns may lead to lower satisfaction and lower quality of medical care. Aim: To explore concerns of hemodialysis patients. Method and material: A Descriptive study on a convenience sample of patients undergoing hemodialysis in dialysis centers in Athens. Data was collected by the completion of a questionnaire which included the patients’ concerns. Categorical variables are presented by absolute and relative frequencies (percentages). Results: In the present study were enrolled 100 patients, of whom 73% were male, 55% were>60 years old, 66% were married and 30% of primary level of education. Regarding patients’ concerns, 36% of participants were bothered to spend time on dialysis center, 65% and 49% were concerned about a possible discontinue of fistula and hemodialysis machine respectively, while 59% were concerned about restrictions in social life, 39% in their role as a spouse, 71% about fluid restrictions, 55% about diet restrictions and 53% were concerned about transport "to and from" hemodialysis unit. In terms of limitations due to hemodialysis, 30% reported limitation in clothes, 69% in going for holidays and 67% in sexual life. Conclusions: Expanding nurses knowledge about patients’ concerns is essential to implement individualized effective therapeutic strategies.